A low scattering slot antenna based on broadband polarization conversion metasurface. Issue 9 (14th May 2019) - Chen, Jiaqing; Zhao, Yongjiu; Jing, Xiang; Ge, Yue; Chen, Xiaofeng
Abstract: An ultrawide band polarization conversion metasurface (PCM) is proposed to reduce the reflection of a slot antenna. The proposed PCM can convert a linearly polarized incident wave to the reflected wave with a 90° rotation. By arranging the PCM around the antenna symmetrically, an ideal phase cancelation is achieved. To verify the design, a metasurface‐slot antenna is simulated and measured to confirm the proposed PCM for a significant reduction of the reflection. Results show that the normal reflection of the proposed antenna at boresight is reduced more than 10 dB over an ultrawide band. In addition, 2 dB enhancement of the gain is achieved compared with a reference antenna which has the same dimensions. Meanwhile, the small influence is observed for the antenna radiation by introducing the PCM.